Security studies : an introduction - Williams, Paul D.; McDonald, Matt (New York : Routledge, 2023)
"Security Studies: An Introduction, 4th edition, is the most comprehensive textbook available on the subject, providing students with in-depth coverage of traditional and critical approaches and an essential grounding in the debates, frameworks, and issues of the contemporary security agenda. This new edition has been completely revised and updated, to cover major developments such as COVID-19, the rise of populism, climate change, China and Russia's place in the world, and the Trump administration. It also includes new chapters on great power rivalry, new technologies, and economic threats. Divided into four parts, the text provides students with a detailed, accessible overview of the major theoretical approaches, key themes, and most significant issues within security studies. Part 1 explores the main theoretical approaches from both traditional and critical standpoints Part 2 explains the central concepts underpinning contemporary debates Part 3 presents an overview of the institutional security architecture Part 4 examines some of the key contemporary challenges to global security Collecting these related strands into a single textbook creates a valuable teaching tool and a comprehensive, accessible learning resource for undergraduates and MA students"--
Third edition: 2018.
Includes bibliographical references and index.
Keywords: Security, International